Effect of some plant extracts on germination and seeding of Raphanus sativus and effect on surface growth ofRhizoctonia solani (Baghdad Science Journal, 2011)
The experiment was conducted to study the effect of leaves extract of Salvia sclarea , Rosmarinus officinalis and Thymus vulgaris with 10% and 30% concentration on germination of seeds and growth of seedlings .The effect of these extracts on infection percentage of seeds decay and surface growth of Rhizoctonia solani .The results showed that the three extracts effected significantly to reduced percentage of seeds germination, acceleration of germination , promoter indicator , infection percentage of seeds decay and surface growth of R. solani especially in 30% concentration .